Preliminary Results of Structural Optimization of Dental Prosthesis Using Finite Element Method - Togashi, M. M. [UNESP]; Andrade, M. P. [UNESP]; Santos, F. J. dos [UNESP]; Hernandez, B. A. [UNESP]; Sousa, E. A. Capello [UNESP] (Springer Nature, 2022)
Despite the high success rate of dental prostheses in treating patients, mechanical failures still occur. Studies about the biomechanical behaviour of dental prostheses are thus important to avoid such failures and to ensure patient’s well-being. This study proposed a parametric and optimization analysis of a dental implant to investigate which implant’s structural parameters are more relevant to prevent failure and improve osseointegration. A mathematical function called response surface was obtained based on Von Misses stresses in the cortical bone, RSM (Response Surface Methodology), DOE (Design of Experiments), and finite element models. A structural optimization analysis was conducted with the objective of minimizing stresses in the cortical bone. In addition to the sensitivity analysis of the parameters, a more agile process to estimate critical stress through equations was presented, providing a faster way of identifying potential failure causes.
Keywords: Biomechanics; Dental prosthesis; Finite element method; Optimization; Parametric analysis